Soft tissue coverage techniques for management of open fractures of tibia (type IIIB) - Meena, Mahaveer; Chavan, Vikas; Ghilley, Sanjay Kumar; Jangir, Nilesh Kumar (International Journal of Research in Orthopaedics, 2020)
Background: Open fractures are surgical emergencies; incidence of open fractures is increasing with more high-energy road traffic accidents. The tibia is exposed to frequent injury because of its location. The need for aggressive debridement, adequate fracture fixation, and early flap coverage in reducing the morbidity cannot be over emphasized. Methods: Treatment of open fracture by immediate debridement and anatomical fracture reduction using external fixator device. Gastrocnemius muscle flap done in upper 1/3 open fractures (type IIIB) with larger defects along with split thickness skin graft (STSG). In middle and lower 1/3 open fractures (type IIIB), fasciocutaneous and soleus muscle flaps done with relatively smaller soft tissue defects and exposed bone with STSG. Results: The study included 15 patients with open tibia fracture Gustillo Anderson type IIIB classified after the initial debridement. Excellent flap takes up was seen in all cases. 11 cases (73.3%) achieved union at the end of 6 months follow-up while 4 cases (26.7%) showed delayed union which required additional procedures like BMI or bone graft. Conclusions: Soft tissue coverage techniques like fascicutaneous flap, gastrocnemius and soleus muscle flap had a definitive role in the management of open fractures of tibia (type IIIB).